An Exophytic Hepatocellular Carcinoma in an Undiagnosed Cirrhotic Liver Mimicking an Intraperitoneal Soft Tissue Sarcoma - Aziz, Mohd Ezane; Ahmed, Farahat Nadeem (IIUM Medical Journal Malaysia, 2022)
Exophytic hepatocellular carcinoma is a rare type of hepatocellular carcinoma (HCC), which may present with a wide variation in clinical presentations and imaging findings. Thus it may cause diagnostic dilemma and may need a multidisciplinary approach management tailored to individual patient for a better outcome. Here we reported a case of a patient with exophytic hepatocellular carcinoma mimicking an intraperitoneal sarcoma.